2021
DOI: 10.1186/s13071-021-04697-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis suggests that Namibian cheetahs (Acinonyx jubatus) are definitive hosts of a so far undescribed Besnoitia species

Abstract: Background Besnoitia darlingi, B. neotomofelis and B. oryctofelisi are closely related coccidian parasites with felids as definitive hosts. These parasites use a variety of animal species as intermediate hosts. North American opossums (Didelphis virginiana), North American southern plains woodrats (Neotoma micropus) and South American domestic rabbits (Oryctolagus cuniculus) are intermediate hosts of B. darlingi, B. neotomofelis and B. oryctofelisi, respectively. Based on conserved regions in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…besnoiti . In addition, the later study (Schares et al, 2021) suggests that a so far unknown Besnoitia species closely related to B. darlingi , B. neotomofelis , B. oryctofelisi ,B. akodoni or B. jellisoni is cycling in Namibian wildlife.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…besnoiti . In addition, the later study (Schares et al, 2021) suggests that a so far unknown Besnoitia species closely related to B. darlingi , B. neotomofelis , B. oryctofelisi ,B. akodoni or B. jellisoni is cycling in Namibian wildlife.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, two studies have managed to detect by molecular techniques Besnoitia spp. DNA in faeces from pond bat (Myotis dasycneme ) in the Netherlands (Hornok et al, 2015) and in faecal matter from cheetahs (Acinonyx jubatus ) in Namibia (Schares et al, 2021); in the first report, authors hypothesized that B. besnoiti -like sequences might have originated from French cattle via bloodsucking dipterans (Stomoxys calcitrans, Tabanus spp.). In this regard, bats frequently use cattle stables for roosting, where they can prey on the mechanical vectors ofB.…”
Section: Resultsmentioning
confidence: 99%
“…Natural infection of horses with B. bennetti were documented in Kenya ( Bwangamoi, 1972 ) and South Africa ( Van Heerden et al, 1993 ). Besnoitia darlingi -like species was found naturally infecting cheetah ( Schares et al, 2021 ), and only in Namibia. Besnoitia infections by unidentified species ( Besnoitia spp.)…”
Section: Resultsmentioning
confidence: 99%
“…Although infections in Africa has only been detected based on clinical signs, histological and pathological examination, exposure or infection of B. bennetti in equids in Europe were detected based on clinical signs, serological test (IFAT and western blot) ( Gutiérrez-Expósito et al, 2017 ) and partial rDNA sequencing ( Liénard et al, 2018 ), which have not been able to conclusively distinguish between species ( Villa et al, 2021 ). Schares et al (2021) isolated and identified B. darlingi -type naturally occurring in cheetah in Botswana based on conventional and real-time PCR. Although reviewed studies showed that this is the only report of B. darlingi -type in sub-Saharan Africa, natural infections of B. darlingi -like have been documented in opossum ( Didelphis marsupialis ) in Panama and Brazil, and D. virginiana in North America) and lizard species ( Basiliscus basiliscus , Ameiva ameiva , A. festiva , A. leptophrys ) from Panama, ( Basiliscus vittatus ) from Belize, ( Ameiva ameiva ) from Brazil, and in rodents ( Akodon montensis ) from Brazil ( Dubey et al, 2003 ; Elsheikha et al, 2003 ; Elsheikha et al, 2004 ; Kiehl et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…To monitor the inhibition of the real-time PCRs, a heterologous plasmid with DNA sequences resembling the enhanced green fluorescent protein (EGFP) gene was added to the reaction mix in all real-time PCRs. The internal control PCR included the primers EGFP1-F, EGFP2-R and the probe EGFP1 as previously reported [83]. Cycling condition for qPCR was as follows.…”
Section: Molecular Analyses Protozoamentioning
confidence: 99%